Bend Faulting at the Edge of a Flat Slab: The 2017 Mw7.1 Puebla‐Morelos, Mexico Earthquake - Diego Melgar; Xyoli Pérez‐Campos; Leonardo Ramirez‐Guzman; Zack Spica; Victor Hugo Espíndola; William C. Hammond; Enrique Cabral‐Cano (Geophysical Research Letters)
Abstract We present results of a slip model from joint inversion of strong motion and static Global Positioning System data for the Mw7.1 Puebla‐Morelos earthquake. We find that the earthquake nucleates at the bottom of the oceanic crust or within the oceanic mantle with most of the moment release occurring within the oceanic mantle. Given its location at the edge of the flat slab, the earthquake is likely the result of bending stresses occurring at the transition from flat slab subduction to steeply dipping subduction. The event strikes obliquely to the slab, we find a good agreement between the seafloor fabric offshore the source region and the strike of the earthquake. We argue that the event likely reactivated a fault first created during seafloor formation. We hypothesize that large bending‐related events at the edge of the flat slab are more likely in areas of low misalignment between the seafloor fabric and the slab strike where reactivation of preexisting structures is favored. This hypothesis predicts decreased likelihood of bending‐related events northwest of the 2017 source region but also suggests that they should be more likely southeast of the 2017 source region.